Revised typification of Campanula sibirica (Campanulaceae). Issue 1 (6th March 2019) - Sennikov, Alexander N.; Tikhomirov, Valery N.
Abstract: The protologue of Campanula sibirica included two taxonomically discordant elements. The first element (two illustrations, depicting a plant from Italy) is identifiable as C. dichotoma, and the second element (one specimen from Siberia at LINN, collected by J.G. Gmelin) belongs to C. sibirica subsp. sibirica . Although the specimen was left unannotated by Linnaeus, it is part of the original material because of its morphological characters and provenance; this is confirmed from the correspondence between Linnaeus and Gmelin. This specimen is designated as the lectotype, and this choice supersedes the earlier "lectotypification" (correctable to neotypification) with a specimen at LINN that was sent to Linnaeus by G.A. Scopoli in 1762.